The Principal's Policy in Improving the Quality of Learning Based on Tahfidz Al-Qur'an at SDI Bustanu Usyuqil Qur'an (BUQ) Lesmana Ajibarang Banyumas - Nurkholis, Nurkholis (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
This study aims to analyze the policies implemented by the Principal of SDI Bustanu Usyuqil Qur'an (BUQ) Lesmana Ajibarang Banyumas in improving the quality of learning based on Tahfidz Al-Qur'an. The method used in this study is a descriptive qualitative approach, focusing on identifying the influence of policies on curriculum development, human resource management, and evaluation systems, which contribute to improving learning outcomes of Tahfidz Al-Qur'an. Data were obtained through interviews with principals, teachers, staff, and students, as well as observation of learning and extracurricular activities and analysis of school documents and official reports. The results were thematically analyzed to identify key themes related to the principal's policy, leadership, and the quality of Tahfidz learning. The research findings show that the policy implemented by the principal focuses on developing a curriculum that suits students' needs and structured Tahfidz learning. The implementation of this policy involves applying the Qiraati method for Tahfidz learning, as well as strict supervision of the program implementation. In addition, periodic evaluations are conducted to ensure the quality of learning and identify areas for improvement. Supervision by the principal and teachers, as well as regular evaluation of learning outcomes, have proven effective in supporting the success of the tahfidz program at SDI BUQ. Overall, SDI BUQ's principal's policy, which is based on needs analysis, structured management, and continuous evaluation, can improve the quality of learning and students' mastery of memorizing the Qur'an. This research makes an essential contribution to the understanding of education policy implementation in Islamic elementary schools, especially in learning Tahfidz Al-Qur'an, and can be a reference for other Islamic schools in designing similar policies.